2005
DOI: 10.1051/0004-6361:20042424
|View full text |Cite
|
Sign up to set email alerts
|

Combination of nulling interferometer and modified pupil for observations of exo-planets

Abstract: Abstract. We consider a combination of two techniques, namely the nulling interferometer and halo suppression by modified pupil such as shaped pupils and apodized square apertures, which achieves very high dynamic range, in order to detect faint extra-solar planets around nearby stars. The effects of the nulling interferometer and the modified pupil are independent and in combination hence multiplied. We show that one can achieve higher dynamic range in the case of a resolved star than with either method alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The multistep APLC concept (Aime & Soummer 2004) illustrates how such a ''cascade'' can simultaneously improve IWA and throughput by designing each step for a lower contrast level. Nishikawa et al (2005) showed how a nulling interferometer can benefit from a CPA, and a similar combination may also be advantageous on a circular pupil (VNC-CPA for example). The entrance pupil apodization required for the APLCs may be performed by a PIAA unit to improve IWA and throughput.…”
Section: Other Coronagraph Designs and Techniques Not Studied In Thismentioning
confidence: 99%
“…The multistep APLC concept (Aime & Soummer 2004) illustrates how such a ''cascade'' can simultaneously improve IWA and throughput by designing each step for a lower contrast level. Nishikawa et al (2005) showed how a nulling interferometer can benefit from a CPA, and a similar combination may also be advantageous on a circular pupil (VNC-CPA for example). The entrance pupil apodization required for the APLCs may be performed by a PIAA unit to improve IWA and throughput.…”
Section: Other Coronagraph Designs and Techniques Not Studied In Thismentioning
confidence: 99%
“…This multi-stage approach was also recently considered for coronagraphy with a combination of a classical Lyot coronagraph and a shaped pupil mask (Chakraborty et al 2005). Another way consists in combining nulling interferometry and coronagraphy (Nishikawa et al 2005). The perfect example of multi-stage coronagraphy is, however, proposed by Aime & Soummer (2003b) with the cascading Multi-Stage Prolate-(amplitude) 1 -Apodized Lyot Coronagraph (MS-PALC).…”
Section: Approachmentioning
confidence: 99%
“…Our simulations suggest that extremely small amplitude and OPD errors would be required for achieving excellent nulling performance such as 10 −10 at 5 λ 0 /D. We note that these requirements would be relaxed by introducing additional high-contrast imaging techniques, such as a pupil apodization, behind the nulling interferometer [23].…”
Section: Simulation Resultsmentioning
confidence: 90%